ANALISIS SISTEM PENYIMPANAN DAN PENGELOLAAN ARSIP DI FAKULTAS USHULUDDIN UNIVERSITAS ISLAM NEGERI SUNAN GUNUNG DJATI BANDUNG - Wulan, Wulan Fauziah; Widwi Handari Adji (JEBS (Journal of Economic and Business Student), 2023)
The purpose of this study was to find out about how the storage and management system of Archives in providing information according to the needs of students and officers of the Faculty of Ushuluddin. The research method used is descriptive qualitative, data collection techniques in this study are observation, interviews, documentation, literature study and internet browsing. After analysis, the results of this study indicate that the archive storage system at the Faculty of Ushuluddin, Sunan Gunung Djati State Islamic University Bandung is basically said to be quite good.There are several problems that occur, namely the absence of forms and control cards for borrowing archives, as well as the lack of infrastructure and archive maintenance. This research is expected to provide convenience in storing and finding back archives. Suggestions from this research should be made borrowing forms and archive control cards, and special archive maintenance should be carried out at least 3 months, maximum 6 months.